2019
DOI: 10.1002/ejlt.201800511
|View full text |Cite
|
Sign up to set email alerts
|

OxPLs‐Masking/Degradation Immune Assay: An “All‐Included” Analysis of Mechanisms Detoxifying Oxidized Phospholipids

Abstract: The manuscript discusses the use of circulating oxidized phospholipids (OxPLs) as potential disease biomarkers. Blood levels of OxPLs have been previously demonstrated to be strongly associated with cardiovascular disease. These data were obtained using an immune assay based on monoclonal antibody E06 which detects oxidized phosphatidylcholine. The impact of other classes of OxPLs on disease progression is not known. It is postulated that 1) other classes of OxPLs may contribute to cardiovascular disease and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Therefore, oxPCs themselves cannot be used as potential biomarkers of NSCLC due to their lack of specificity. However, Philippova et al (2019) pointed out that simultaneous determination of plasma levels of oxPCs and estimation of the detoxifying capacity of plasma to neutralize these lipids can significantly improve the diagnostic importance of oxPCs as a disease biomarker. In the context of our results, oxPCs might be rather considered as potential markers to distinguish between different NSCLC subtypes instead, however this requires more investigation, including the quantification of these lipids in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, oxPCs themselves cannot be used as potential biomarkers of NSCLC due to their lack of specificity. However, Philippova et al (2019) pointed out that simultaneous determination of plasma levels of oxPCs and estimation of the detoxifying capacity of plasma to neutralize these lipids can significantly improve the diagnostic importance of oxPCs as a disease biomarker. In the context of our results, oxPCs might be rather considered as potential markers to distinguish between different NSCLC subtypes instead, however this requires more investigation, including the quantification of these lipids in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…OxPC species, particularly fragmented forms, are bioactive and can rapidly interact with plasma proteins ( 9 ). Philippova et al ( 26 ) also suggested that in OxPC analysis, results of LC-MS/MS and immunoassay are related but not duplicates, as they observed weak correlations between free levels of 8 OxPC species measured by LC-MS/MS and E06 antibody in plasma of patients that underwent coronary angiography. They suggested that E06 recognizes both free form and covalent adducts of OxPCs which are bound to lipoproteins, cell membranes and other plasma proteins.…”
Section: Discussionmentioning
confidence: 99%